Sarcopenia and inflammatory bowel disease: a literature review - Silva, Joana Patrícia Oliveira Martins da (2021)
Introduction: Sarcopenia is a disease characterized by the progressive loss of skeletal muscle strength and mass. This condition is a prognostic factor for several pathologies and can affect individuals at any age, with a significant incidence in chronic inflammatory states, such as Inflammatory Bowel Disease (IBD). Aim: To present an overview on the current evidence regarding sarcopenia and nutritional management of this condition among IBD patients. Results: IBD patients are at risk of developing sarcopenia and this must be taken considered in order to minimize the occurrence of further adverse clinical outcomes. Regarding strategies for the prevention and treatment of sarcopenia in IBD patients, the most commonly used strategies are oral nutritional supplements and enteral nutrition, supplementation with vitamin D and omega 3 fatty acids (associated with decreased inflammatory activity), combined with regular practice of physical activity, in order to maintain or increase muscle mass and function. Nevertheless, there are no specific guidelines concerning the prevention or treatment of sarcopenia in IBD patients. Conclusion: The current evidence about sarcopenia in IBD patients is still scarce. Nevertheless, the early identification of sarcopenia in IBD patients if of utmost importance for an effective intervention. Further research is needed in order to establish specific guidelines for the identification and management of sarcopenia in IBD patients and also to reach a consensus in the most effective nutritional strategies.